Evaluation of the Vocational’s Teaching Factory Program on Multimedia Competencies through the CIPP Model - Yuniardi, Gigih Dwi; Isnandar, Isnandar; Patmanthara, Syaad; Zulfikar, Nizam Muchammad (Graduate School of Universitas Negeri Malang, 2023)
This research aims to assess the Teaching Factory (TEFA) program using the Context, Input, Process, Product (CIPP) evaluation model. The program is implemented in vocational schools, which refers to the standards and procedures applicable in the current industry. In this study, Muhammadiyah 7 Gondanglegi Vocational School will be the research subject. The CIPP evaluation model was carried out by collecting data using observation, interviews, and questionnaires, and then it will analyzed using a percentage descriptive system. The research results show that the TEFA program is in good criteria in all four aspects. However, its implementation can improve several points, such as the infrastructure, laboratories, or practical workshops.